PENINGKATAN MOTIVASI BELAJAR IPA MELALUI IMPLEMENTASI METODE INQUIRY KELAS V SEKOLAH DASAR - Mahlianurrahman, Mahlianurrahman (Jurnal Ilmiah Sekolah Dasar, 2017)
This research was motivated by the low of motivation learning of class V students of Pasi Pinang elementary School academic year 2016/2017. This research was held to decribe the effort to improve motivation learning by using inquiry methods and improve learning motivation by using inquiry methods in science. The type of this research was class V students of Pasi Pinang Elementary School year academic 2016/2017 school year which had 24 students. The object of this research was the improvement of studentsâ motivation using inquiry methods in science subject. The results of this research showed that the use inquiry methods can improve studentsâ motivation learning in learning science subject in class V Pasi Pinang Elementary School academic year 2016/2017.